Management consulting projects : a step-by-step experiential guide - Cook, Ronald G.; Harris, Michael, 1970- (New York : Routledge, 2021)
"This textbook provides students with an easy to use, proven roadmap for completing a successful consulting project from start to finish. Primarily designed for students who work as outside consultants on solving client problems and investigating potential opportunities, the textbook's structure first explains the consulting process to students and then depicts it in a chronological flow, using real-life examples to demonstrate practical application. Each section builds upon the previous one, focusing on the development of critical thinking, problem solving, and communication skills for employability. Now in its 6th edition, this text has been fully revised to bring it up to date with the current business context and global environment, including: A major expansion of the tools and resources needed for students to conduct research on a client's situation. A new final chapter that ties the overarching consulting process together and focuses on how the student should use this experience for their own professional development. New examples of award-winning projects to provide practical guidance. Fresh material on the use of new technologies in the consulting process, ethics and data management, and remote working. This well-renowned model promotes a conceptual understanding of the consulting process and the interactions between and among students, the team, the client and the instructor. Management Consulting Projects should be essential reading for experiential Business Consulting modules, Small Business Management and Strategic Management at postgraduate and MBA level"--
Revised edition of The experiential student team consulting process, c2016.
Keywords: Business consultants -- Training of -- Handbooks, manuals, etc; Experiential learning -- Study and teaching -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Consulting; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Management